Distribution patterns of the Peruvian species of Senecio L. (Asteraceae) - Beltrán, Hamilton (2022)
This paper analyses the distribution of Peruvian species of the genus Senecio, based on 4342 herbarium sheets with available localities and geographical coordinates. The Rivas-Martínez method of bioclimatic belts and the Köppen-Geiger model were used to determine how they are related to climate, and to observe their response in the face of climatic changes over 50 and 100 years. To observe the departmental distribution of the species and the relationship between departments in terms of presence-absence (UPGMA, Sørensen's coefficient) was used. A Principal Component Analysis (PCA) revealed the correlation of each species with mean altitude, mean climatic variables and mean Thermicity Index of the localities of a species, establishing 10 groups ordered by bioclimatic belts. Different distribution patterns were mapped, corresponding to bioclimatic belts and biogeographical provinces of Peru. The Cordillera Blanca forms an authentic biogeographical barrier separating numerous localities in northern Peru from the rest of the Senecio positions.